Variability and performance of NHS England’s ‘reason to reside’ criteria in predicting hospital discharge in acute hospitals in England: a retrospective, observational cohort study - Elizabeth Sapey; Simon Ball; David McNulty; Felicity Evison; Suzy Gallier; Katherine Reeves (BMJ Open)
Objectives NHS England (NHSE) advocates ‘reason to reside’ (R2R) criteria to support discharge planning. The proportion of patients without R2R and their rate of discharge are reported daily by acute hospitals in England. R2R has no interoperable standardised data model (SDM), and its performance has not been validated. We aimed to understand the degree of intercentre and intracentre variation in R2R-related metrics reported to NHSE, define an SDM implemented within a single centre Electronic Health Record to generate an electronic R2R (eR2R) and evaluate its performance in predicting subsequent discharge.Design Retrospective observational cohort study using routinely collected health data.Setting 122 NHS Trusts in England for national reporting and an acute hospital in England for local reporting.Participants 6 602 706 patient-days were analysed using 3-month national data and 1 039 592 patient-days, using 3-year single centre data.Main outcome measures Variability in R2R-related metrics reported to NHSE. Performance of eR2R in predicting discharge within 24 hours.Results There were high levels of intracentre and intercentre variability in R2R-related metrics (p<0.0001) but not in eR2R. Informedness of eR2R for discharge within 24 hours was low (J-statistic 0.09–0.12 across three consecutive years). In those remaining in hospital without eR2R, 61.2% met eR2R criteria on subsequent days (76% within 24 hours), most commonly due to increased NEWS2 (21.9%) or intravenous therapy administration (32.8%).Conclusions Reported R2R metrics are highly variable between and within acute Trusts in England. Although case-mix or community care provision may account for some variability, the absence of a SDM prevents standardised reporting. Following the development of a SDM in one acute Trust, the variability reduced. However, the performance of eR2R was poor, prone to change even when negative and unable to meaningfully contribute to discharge planning.